Rice price stabilization in Bangladesh: an analysis of policy options - Dorosh, Paul A.; Shahabuddin, Quazi (International Food Policy Research Institute, 2002)
To meet its overall objective of ensuring food security for all households, the Government of Bangladesh undertakes several activities: it intervenes in markets to stabilize prices, targets food distribution to poor households and provides emergency relief after natural disasters. This paper provides measures of the variability of domestic and international rice prices, and examines the mix of government intervention and private sector participation in rice markets. The analysis shows that the relatively high degree of price stability achieved in the 1990s was due in large part to private sector imports that stabilized markets following major production shortfalls. Domestic rice procurement contributed relatively little to raising domestic producer prices at harvest time, involved only a small percentage of farmers, and incurred excessive costs following successful harvests because of procurement prices set far in excess of market prices."